VICE-CHANCELLOR PAYS TRIBUTE TO USM COMMUNITY WHO ASSISTED FLOOD VICTIMS - MPRC, Pusat Media & Perhubungan Awam (USM, 2014)
KOTA BAHARU, 30 December 2014 Universiti Sains Malaysia (USM) ViceChancellor Professor Dato’ Dr. Omar Osman paid tribute to the entire university community who had worked hard to assist the flood victims despite the various hardships they and their own families are going through.